Standarisasi kewajiban nafkah keluarga dalam Al-Quran dan Hadits - Fatah, Nasrul; Ridwan, Ridwan; Ismail, Hidayatullah (Al-Aulia: Jurnal Pendidikan dan Ilmu-Ilmu Keislaman, 2024)
A marriage cannot be separated from the consequences of providing maintenance from a husband to his wife and children. At the level of reality, the provision of maintenance is often a polemic and a source of problems in family life. It is even used as an excuse to end the marriage relationship or delay the marriage. The data shows that of the existing number of divorces, the reason for maintenance is one of the highest causes, as well as the decline in marriage rates due to a feeling of lack of stability on the part of prospective husbands. For this reason, this study seeks to explore the theological guidance from the Qur'an and Hadith regarding the standardization of the obligation of maintenance from a husband to his family. This research is conducted with a maudhu'i or thematic interpretation approach. From this research it was found that in the Qur'an and hadith there is no standard provision regarding the amount of nafkah that must be given, but rather adjusts to the ability and condition of the husband. If it is in a spacious situation, then nafkah should be given with a spacious amount. Conversely, if it is in a tight situation, it should be adjusted.